PETROGENESIS AND RARE METAL MINERALIZATION OF THE ALKALINE GRANITIC MAGMA: A CASE STUDY FROM THE BOZIGUO’ER RARE METAL GRANITIC INTRUSION - He Huang; Tao Wang; Zhaochong Zhang; Qie Qin (Геодинамика и тектонофизика, 2017)
The origination and differentiation of rare metalbearing, alkaline granites has attracted extensive interests because of their economic significance.